An Unusual Case of Ipsilateral Hemiparesis in a Patient with Small Hypertensive Supratentorial Hemorrhage - Fadhlan Abdur Rahman; Septy Aulia Rahmy; Dwi Ayu Novinda Sari; Fahmi Syahtama Hasyim; Avie Baldana Bi'izzyk (AKSONA, 2026)
Highlight: Ipsilateral hemiparesis after supratentorial stroke is a rare neurological presentation. Recurrent stroke may cause ipsilateral motor deficits due to prior corticospinal tract injury. Recognition of this atypical presentation may improve diagnosis and understanding of motor pathway reorganization.   ABSTRACT Introduction: Ipsilateral hemiparesis following supratentorial stroke is a rare neurological presentation that contradicts the typical contralateral motor deficit caused by corticospinal tract decussation. The underlying mechanism remains poorly understood and has most commonly been associated with previous contralateral cerebral injury and motor pathway reorganization. We report a rare case of recurrent supratentorial hemorrhagic stroke presenting with ipsilateral hemiparesis. Case: A 59-year-old woman presented with acute worsening of right-sided hemiplegia and dysarthria that began approximately 2.5 hours before presentation. She had experienced a history of stroke two years earlier, resulting in persistent right-sided motor weakness, as well as poorly controlled hypertension. Neurological examination demonstrated ipsilateral upper motor neuron hemiplegia and facial palsy. Brain CT revealed a small right thalamic intracerebral hemorrhage, consistent with acute intracerebral hemorrhage. Conclusion: The patient had Ipsilateral motor weakness . This rare clinical presentation may be associated with abnormal corticospinal tract anatomy, such as the presence of non-decussating corticospinal fibers, or with compensatory reliance on the ipsilateral corticospinal tract following contralateral tract injury from a previous cerebrovascular event. However, these proposed mechanisms could not be confirmed because advanced neuroimaging modalities, including magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI) tractography, were unavailable. Further studies using advanced neuroimaging are warranted to better characterize the underlying motor pathway reorganization.